Multimorbidity: What Do We Know? What Should We Do? - Rokas Navickas; Vesna-Kerstin Petric; Andrea B. Feigl; Martin Seychell (Journal of Comorbidity, 2016)
Multimorbidity, which is defined as the co-occurrence of two or more chronic conditions, has moved onto the priority agenda for many health policymakers and healthcare providers. Patients with multimorbidity are high utilizers of healthcare resources and are some of the most costly and difficult-to-treat patients in Europe. Preventing and improving the way multimorbidity is managed is now a key priority for many countries, and work is at last underway to develop more sustainable models of care. Unfortunately, this effort is being hampered by a lack of basic knowledge about the aetiology, epidemiology, and risk factors for multimorbidity, and the efficacy and cost-effectiveness of different interventions. The European Commission recognizes the need for reform in this area and has committed to raising awareness of multimorbidity, encouraging innovation, optimizing the use of existing resources, and coordinating the efforts of different stakeholders across the European Union. Many countries have now incorporated multimorbidity into their own healthcare strategies and are working to strengthen their prevention efforts and develop more integrated models of care. Although there is some evidence that integrated care for people with multimorbidity can create efficiency gains and improve health outcomes, the evidence is limited, and may only be applicable to high-income countries with relatively strong and well-resourced health systems. In low- to middle-income countries, which are facing the double burden of infectious and chronic diseases, integration of care will require capacity building, better quality services, and a stronger evidence base.